Sex Differences in Associations Between Socioeconomic Status and Incident Hypertension Among Chinese Adults - Ma, Han; Liu, Fangchao; Li, Jianxin; Chen, Jichun; Cao, Jie; Chen, Shufeng; Liu, Xiaoqing; Yang, Xueli; Huang, Keyong; Shen, Chong; Yu, Ling; Zhao, Yingxin; et al. (Hypertension (Dallas, Tex. 1979), 2023)
With rapid socioeconomic development and transition, associations between socioeconomic status (SES) and hypertension remained uncertain in China. We aimed to examine the health effects of SES on hypertension incidence and explore the sex differences among Chinese adults. We included 53 891 participants without hypertension from the China-PAR (Prediction for Atherosclerotic Cardiovascular Disease Risk in China) project. SES was evaluated by education level, occupation prestige, and household monthly per capita income, and categorized into low, medium, and high groups. Hazard ratios and their 95% CIs were calculated using Cox proportional hazards regression models. Compared with high SES, participants with medium SES (hazard ratio, 1.142 [95% CI, 1.068-1.220]) or low SES (hazard ratio, 1.166 [95% CI, 1.096-1.241]) had increased risks of incident hypertension in multivariate analyses. Interactions between SES and sex on hypertension were observed, with more pronounced adverse effects of lower SES among women. The corresponding hazard ratios (95% CIs) for low SES group were 1.270 (1.155-1.397) for women and 1.086 (0.999-1.181) for men. Effects of occupation prestige on hypertension were the strongest among SES factors. Our study provided the compelling evidence from China that lower SES was associated with incident hypertension and women were more susceptible. These findings will have substantial implications on future hypertension prevention and management, especially among women. Sex-specific approaches are warranted to reduce socioeconomic disparities.